COMPLICATIONS OF RECONSTRUCTION PLATE INSTALLATION IN MANDIBULAR - Leni Ruslaini; Asri Arumsari; Abel Tasman; Kiki Akhmad Rizki (Dentino : Jurnal Kedokteran Gigi, 2021)
Background: Mandibular resection will cause mandibular stability disturbance due to loss of some part of the bone. Instability of the mandible can cause aesthetic, physiological, and psychological malfunction. Installment of mandibular reconstruction plat on the remaining mandibular using screws were suggested to restore its stability. However, it is not uncommon that plat exposure occurs following mandibular reconstruction, caused by inaccurate adaptation of the plats to the mandibular bone. The aims of this report are to describe the various complications and managements after jaw resection and reconstruction with plates. Case Report: A 44 years old male patient complained the small defect in the chin, painless, and no fluid emited, accompanied by dermatitis. Intra oral examination showed no abnormalities. About 1 year ago the patient performed segmental resection of the mandible on the indication of ameloblastoma. The radiological x-ray showed all screw detached from the plat and radiolucent images appeared around the plat that attached to the mandible. The diagnosis was fistula at regio mentale, post resection and reconstruction surgery, suspected caused by titanium plate allergies. The provided therapies were fistulectomy, screw removal, and plate reconstruction. Post therapy conditions showed improvement and no patients complaints of pain. Conclusion: Plate exposure is a complication that can occur after the installation of the reconstruction plate, but besides that it can also cause an allergic reaction from the material used. Keywords: Complication, Mandibular Resection, Plate Reconstruction, Titanium Plate Allergies